عصری اردو تفاسیرمیں سائنسی اسلوبِ کی دعوتی اہمیت: Da’wah Importance of Scientific Style in Modern Urdu Tafasīr (Al-Qamar, 2021)
Praise be to Allah. There are a large number of commentaries in Urdu commentaries that illustrate the scientific style of the Quran. In the Quran, Allah Almighty has encouraged people to look, think and examine in a scientific manner and has given the ability to solve all the problems. He also invited us to analyze in such a way that the questions that arise in the human mind can be answered and satisfaction can be obtained. For this, Allah Almighty says, "Who created the things of the universe?" Who is their creator? Along with this, there is also the matter of analyzing and examining in the Qur'an what was the fate of those who obeyed and disobeyed Allah Almighty, i.e. those who believe in Allah and disobedient are not equal because the destruction of the disobedient is in front of everyone. Therefore, a beautiful method of calling people to the Day of Judgment, which is called the scientific style, has made it possible for those who have intellect and wisdom to accept the message of truth. This is the miracle of the Quran.
Keywords: Tafasīr; Science; Methods; Da'wah